PROBLEMS OF CRUSH-LEACH ANALYSES OF LOW-SALINITY INCLUSION-POOR MATERIAL - Christie A.B.; Goguel R.L.; Robinson B.W. (My University, 1989)
We present analyses which suggest that single or multiple water leaches of low-salinity fluid inclusions are suspect and their application to chemical geothermometry is likely to give erroneous results.Leaching experiments were conducted on 20 quartz and 1 calcite sample from epithermal veins in the Hauraki Goldfield, New Zealand, and 1 calcite drill-cutting sample from the Ngawha geothermal area. Each sample was crushed under vacuum in stainless-steel tubes and leached with a series of solvents. A three-stage leaching technique using water, neutral-pH ammonium nitrate solution and 13% nitric acid solution was finally adopted. This process is designed to leach the fluid inclusions, remove ions adsorbed on the crushed mineral surfaces, and additionally indicate the presence of contamination from the host mineral and contained solid inclusions. Most of our analyses show contamination of Al, Ca, Li, Mg and, where analysed, Zn. A few are also contaminated by Na, K, Cl, Cs and Rb. Least contaminated analyses (11) indicate that the Hauraki epithermal fluids sampled had salinities between 0.3 and 2.4 wt.% with an average value of 1.0 wt.%.